This research to study relation between environment parameter, plankton abundance and primary productivity with abundance of tiger prawn post larvae and milk fish fry, calculates plankton predating rate speed by tiger prawn post larvae and milk fish fry and other larva and studies plankton population dynamics, tiger prawn post larvae and milk fish fry before, at the time and after peak season. Result of research indicates that some environment parameters significant differs according to observa - Nur Asia Umar; Richardus F. Kaswadji; Ario Damar; Ismudi Muchsin; I Wayan Nurjaya (Forum Pasca Sarjana, 2009)
This research to study relation between environment parameter, plankton abundance and primary productivity with abundance of tiger prawn post larvae and milk fish fry, calculates plankton predating rate speed by tiger prawn post larvae and milk fish fry and other larva and studies plankton population dynamics, tiger prawn post larvae and milk fish fry before, at the time and after peak season.  Result of research indicates that some environment parameters significant differs according to observation period and season.  Highest abundance of tiger prawn post larva, milk fish fry and other larva reaches to 29067, 7733 and 54400 ind/1000 m3. Highest grazing rate to population of phytoplankton and plankton (phytoplankton + zooplankton) found when predator consisted of tiger prawn post larva, milk fish fry and other larva with grazing rate up to 125 cells/liter/hour and 129 plankter /liter/hour respectively.  Highest predating rate to zooplankton population when predator consist of tiger prawn post larva and milk fish fry and there is phytoplankton as their prey up to 12 individual/liter/hour.  The certain plankton species significant correlation and estimated as natural food of tiger prawn post larva and milk fish fry that is some types of diatom and crustaceae from zooplankton.  Plankton population dynamics especially controlled by predator by tiger prawn post larva, milk fish fry and other larva, while influence of environment parameter is small relative. Abundance of each phytoplankton and zooplankton ranged from 583-28563 cells/liter and 22-3413 ind/liter.  Average abundance of phytoplankton and zooplankton significant differs higher at peak season compare  before and after tiger prawn post larva and milk fish fry season. Predator-prey relation between phytoplankton and zooplankton shows phase change which succession between phytoplankton controls to zooplankton phases with zooplankton control to phytoplankton.  Abundance of plankton influences abundance of population of tiger prawn post larva and milk fish fry especially after peak season.  There is concordance of time between peak abundance of tiger prawn post larva and milk fish fry and other larva with peak abundance of phytoplankton and zooplankton.   Key words : population dynamics, predating, predating rate, predator, prey, phytoplankton, zooplankton, tiger prawn post larva, milk fish fry, other larva, Pinrang